Aspectos do positivismo em Machado de Assis - Silva, Edilza Maria (2009)
Machado de Assis in his writings has approached some aspects of the thought of Auguste Comte. It was searched, through the analysis of the texts of that author, focusing mostly his chronicles; identify how the writer positions himself facing the important ideas for the development of science of his period. It is worth emphasizing that the analyzed texts are contemporary to the spread of positivism in Brazil. In the last phase of his life, Comte created the Religion of Humanity known as religious positivism, whose ideas are expressed in his Positivist Catechism. In the mid-nineteenth century, these ideas became widespread in Brazil. In 1881, in Rio de Janeiro, under the direction by Miguel Lemos, was inaugurated the Positivist Church of Brazil, based on the precepts of the Religion of Humanity, founded by Auguste Comte. The religious temple became the place for meetings and debates of Republican and abolitionist adepts of positivism that is guided by the ideals of the Positivist Church. The Proclamation of the Republic and abolition, events influenced by positivism, were approached often by Machado de Assis